Glycemic control and fracture risk in elderly patients with diabetes. (May 2016) - Conway, Baqiyyah N.; Long, Dustin M.; Figaro, M. Kathleen; May, Michael E.
Highlights: The relationship of glycemic control and fracture in elderly patients with diabetes was assessed. An HbA1c between 6.5% and 6.9% was optimal for minimizing fracture risk. Risk associated with n HbA1c ≥9% may be an indicator of less frequent patient-provider interaction. Abstract: Aims: Elderly patients with diabetes are at increased fracture risk. Although long exposure to hyperglycemia may increase fracture risk via adverse effects on bone metabolism, tight glycemic control may increase risk via trauma subsequent to hypoglycemia. We tested the prospective relationship between glycemic control and fracture risk in 10, 572 elderly patients (age ≥65) with diabetes. Methods: Geriatric patients with diabetes were drawn from Vanderbilt University Medical Center's Electronic Health Record. Baseline was defined as age at first HbA1c after the latter of age 65 or ICD 9 code for diabetes. Cox analysis was used to test the relationship of updated mean HbA1c (average HbA1c over follow-up) with time to first fracture since baseline. HbA1c was categorized as follows: <6.5% [<48 mmol/mol]; 6.5–6.9% [48–52 mmol/mol]; 7–7.9% [53–63 mmol/mol]; 8–8.9% [64–74 mmol-mol]; ≥9% [≥75 mmol/mol]. The number of BMI measurements was used as a surrogate for relative frequency of outpatient visits, i.e. patient-provider contacts. Results: During follow-up, there were 949 fracture events. HbA1c demonstrated a cubic relationship with fracture risk ( p < 0.05). In analyses accounting for age, sex, race, and number of BMI measures (a surrogate for patient-provider interaction), compared to an HbA1c of 7–7.9%, HRs (95% CIs) were: HbA1c < 6.5% HR = 0.97 (0.82–1.14), 6.5–6.9% HR = 0.80 (0.66–0.97), 8–8.9% HR = 1.13 (0.92–1.40), ≥9% HR = 1.19 (0.93–1.54). Conclusions: An HbA1c of 6.5–6.9% is associated with the lowest risk of fracture in elderly patients with diabetes. Risk associated with an HbA1c ≥9% may be a marker of infrequent patient-provider interaction.